2002
DOI: 10.1562/0031-8655(2002)075<0585:peobat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Boldo and Tea Infusions on the Visible Light–mediated Pro-oxidant Effects of Vitamin B2, Riboflavin¶

Abstract: The effect of Boldo and black tea infusions on the pro-oxidant effects of vitamin B2, riboflavin (RF), when exposed to the action of visible light was studied. The amounts of antioxidants present in Boldo and tea infusions were evaluated by a procedure based on the bleaching of preformed 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cations and were expressed as 6-hydroxy-2,5,7,8-tetramethyl-chroman-2-carboxylic acid equivalent concentrations. The quenching rate constants of singlet oxygen (1O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Boldo hydroalcoholic extract present a relevant hepatoprotective effect and boldine was at least partially responsible for the reported liver protecting but not for the anti-inflammatory effect [10]. The in vitro antioxidant effect of herbal teas consumed in Chile, including P. boldus leaf infusion was reported [9,11,12]. In a previous communication [7], we showed that catechin was one of the antioxidant compounds of boldo leaves, and that the relative concentration of alkaloids and phenolics in boldo extracts suggested that free-radical scavenging effect is mainly due to catechin and flavonoids rather than to the aporphine alkaloids content.…”
Section: Introductionmentioning
confidence: 86%
“…Boldo hydroalcoholic extract present a relevant hepatoprotective effect and boldine was at least partially responsible for the reported liver protecting but not for the anti-inflammatory effect [10]. The in vitro antioxidant effect of herbal teas consumed in Chile, including P. boldus leaf infusion was reported [9,11,12]. In a previous communication [7], we showed that catechin was one of the antioxidant compounds of boldo leaves, and that the relative concentration of alkaloids and phenolics in boldo extracts suggested that free-radical scavenging effect is mainly due to catechin and flavonoids rather than to the aporphine alkaloids content.…”
Section: Introductionmentioning
confidence: 86%
“…Rf is an excellent natural photosensitizer that generates reactive oxygen species under light irradiation and can induce amino acid and protein oxidation . Namely, it is involved in the photodecomposition of free or protein-bound amino acids including tryptophan and tyrosine , and the photoinactivation of enzymes including lysozymes. In addition, it promotes the photodegradation of folic acid to 6-carboxypterin .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, lumichromes are formed as products during the photochemical reactions of riboflavin. Triplet state riboflavin mediates the photodegradation of free or protein-bound amino acids such as tryptophan and tyrosine , and initiates the photoinactivation of enzymes such as lysozyme. Although the FAD/FAD •– couple can vary greatly depending on the protein, FAD* is high enough in energy (∼2.5 V) to readily oxidize Trp and Tyr, but not Phe, whose redox potential is substantially higher (>2.2 V, Table ) and may exceed that of the peptide backbone .…”
Section: Key Endogenous Photosensitizers and Their Targetsmentioning
confidence: 99%